Innovation by demand: An interdisciplinary approach to the study of demand and its role in innovation - Tomlinson, Mark (Manchester University Press, 2002)
The structure and regulation of consumption and demand has recently become of great interest to sociologists and economists alike, and at the same time there is growing interest in trying to understand the patterns and drivers of technological innovation. This book brings together a range of sociologists and economists to study the role of demand and consumption in the innovative process. The book starts with a broad conceptual overview of ways that the sociological and economics literatures address issues of innovation, demand and consumption. It goes on to offer different approaches to the economics of demand and innovation through an evolutionary framework, before reviewing how consumption fits into evolutionary models of economic development. Food consumption is then looked at as an example of innovation by demand, including an examination of the dynamic nature of socially-constituted consumption routines. The book includes a number of illuminating case studies, including an analysis of how black Americans use consumption to express collective identity, and a number of demand-innovation relationships within matrices or chains of producers and users or other actors, including service industries such as security, and the environmental performance of companies. The involvement of consumers in innovation is looked at, including an analysis of how consumer needs may be incorporated in the design of high-tech products. The final chapter argues for the need to build an economic sociology of demand that goes from micro-individual through to macro-structural features.